The Role of Physical Culture in Human Life - Qudiyarov Ikram Maratovich (Zien Journals, 2022)
This article is devoted to the definition of the role of physical culture in human life. The article also analyzes the impact of physical exercise on the human body and considers the need for physical development.
Keywords: Physical culture; health promotion; healthy lifestyle; physical activity